2006
DOI: 10.1126/science.1128245
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Polar Ethane Cloud on Titan

Abstract: Spectra from Cassini's Visual and Infrared Mapping Spectrometer reveal the presence of a vast tropospheric cloud on Titan at latitudes 51 degrees to 68 degrees north and all longitudes observed (10 degrees to 190 degrees west). The derived characteristics indicate that this cloud is composed of ethane and forms as a result of stratospheric subsidence and the particularly cool conditions near the moon's north pole. Preferential condensation of ethane, perhaps as ice, at Titan's poles during the winters may part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
144
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(158 citation statements)
references
References 32 publications
13
144
0
1
Order By: Relevance
“…2c). A discrete ordinates radiative transfer calculation with 32 streams is used (Griffith et al 2006), which adopts the opacity profile derived by the Huygens probe (Tomasko et al 2008a(Tomasko et al , 2008b al. 1991) indicate that only ∼10% of the surface insolation, ∼0.037 W m Ϫ2 (roughly the amplitude of seasonal insolation variations at tropical latitudes), is available for evaporation and convection.…”
Section: Titan's Tropospheric Humiditymentioning
confidence: 99%
“…2c). A discrete ordinates radiative transfer calculation with 32 streams is used (Griffith et al 2006), which adopts the opacity profile derived by the Huygens probe (Tomasko et al 2008a(Tomasko et al , 2008b al. 1991) indicate that only ∼10% of the surface insolation, ∼0.037 W m Ϫ2 (roughly the amplitude of seasonal insolation variations at tropical latitudes), is available for evaporation and convection.…”
Section: Titan's Tropospheric Humiditymentioning
confidence: 99%
“…Numerous cloud features have also been detected from ground-based observations (e.g. Griffith et al 2000) and Cassini observations (Griffith et al 2005(Griffith et al , 2006Porco et al 2005). Even though some of the observed features have been speculated to be indicative of cryovolcanic activities (Roe et al 2005), most of the observed features can be understood in the framework of the general circulation model of Titan's atmosphere (Rannou et al 2006;Rodriguez et al 2007) and do not require any particular activity on Titan's surface.…”
Section: Observational Constraints On the Evolution Of Titan And Its mentioning
confidence: 95%
“…As on Earth, the clouds on Titan are varied in origin. Cassini has variously seen convective "thunderstorm" clouds (but without the thunder; [45]), fog [23], lake-effect clouds [22], and polar ethane clouds [46]. All of these clouds have different optical depths and heights, and evolve with time.…”
Section: Task 22amentioning
confidence: 99%